Correlation Analysis Study Between Spent Mushroom Substrate and Microbial Community - In Kyu Lee; Hyun Seung Kim; Ji Min Woo; Won Jun Chang; Eun Jeong Byeon; Ki Byung Park; Youn Su Lee (한국균학회지)
Next-generation sequencing of shiitake, oyster, and king oyster spent mushroom substrates collected from Chun-cheon, Yeo-ju, Hong-cheon, Gwang-ju, Ui-ryeong, and A-san was performed. Metabarcoding analysis using amplicon sequence variants was performed to confirm the microbial content ratio in the medium after harvesting the collected mushrooms; the ratio of the contents of various microorganisms in the medium after mushroom harvest varied depending on the materials added to produce the mushroom medium. The WPGMA analysis of the similarity between microbial communities, which was based on the β-diversity, confirmed that the microbial communities in the substrates of the different mushroom varieties were similar.